Важнее, чем любовь: женские истории Виктории Токаревой : [сборник] / Виктория Токарева - Токарева Виктория Самойловна (АСТ, 2007)
Экземпляры: ф.6 (20171229) / Инвентарный номер: 2265 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Т 51 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6-44